A huge impact on reading. (1st September 2019) - Lee-Potter, Emma
Abstract : From reading challenges to awards and visits, Ros Harding – the School Librarian of the Year 2019 – has been recognised for the wide range of literacy initiatives she undertakes with students. Emma Lee-Potter finds out more